Supine-exercise-induced oxygen supply to the right myocardium is attenuated in patients with severe idiopathic pulmonary arterial hypertension. Issue 24 (31st August 2011) - Wong, Yeun Ying; Raijmakers, Pieter G; Knaapen, Paul; Lubberink, Mark; Ruiter, Gerrina; Marcus, J Tim; Boonstra, Anco; Lammertsma, Adriaan A; Westerhof, Nico; van der Laarse, Willem J; Vonk-Noordegraaf, Anton
Abstract : Background: Impaired right ventricular (RV) myocardial blood flow (MBF) has been associated with RV dysfunction and fatal RV failure in idiopathic pulmonary hypertension during stress. MBF and O2 extraction from myocardial capillaries (O2 extraction fraction (OEF)) influence myocardial O2 supply. Objective: To determine how the baseline RV OEF affects the amount of MBF increase induced by supine exercise, the authors hypothesise that higher baseline OEF (H-OEF) results in limited O2 extraction during exercise and that MBF must therefore be increased to obtain sufficient O2 . Methods: In 18 patients with idiopathic pulmonary hypertension, baseline OEF, resting MBF and exercise-induced MBF at 40% of maximal cardiopulmonary exercise testing load were measured using positron emission tomography and [ 15 O]O2, [ 15 O]H2 O and [ 15 O]CO. Results: For the whole population, exercise increased RV MBF from 0.68±0.16 to 1.13±0.38 ml/min/g (p<0.0001). The MBF exercise-to-rest ratio (reserve) was 1.7±0.7. The median baseline OEF was 0.73 at which the patient population was split into H-OEF and lower baseline OEF (L-OEF). Baseline MBF values (0.61±0.11 and 0.74±0.17 ml/min/g, respectively) were similar, and exercise induced a significant MBF increase in both groups (p=0.0001). However, exercise-induced increase in MBF was significantly less in the H-OEF group than in the L-OEF group (0.97±0.30 and 1.30±0.39 ml/min/g, respectively, p<0.05). Moreover, H-OEF patients had lower baseline stroke volume and cardiac output than the L-OEF group (52±19 ml and 4.0±1.1 l/min vs 78±18 ml and 5.5±0.9 l/min, respectively, both p<0.05). Conclusions: H-OEF patients were hemodynamically poorer and showed a lower exercise-induced MBF increase compared to L-OEF patients, suggesting exercise-induced O2 supply limitation.